1931 Colo. Sess. Laws 399 - (:unkn) unknown (My University, 1931)
Ch. 97, § 2: Prohibited the discharge of any gun, rifle, pistol, shot gun, or other firearm from any aircraft, airplane, airship while the same is in motion, with the intent or purpose to take, capture, kill, or attempt to kill any migratory bird.
Keywords: HUNTING REGULATION